Collapse and revival : understanding global recessions and recoveries - Kose, M. Ayhan; Terrones, Marco (International Monetary Fund, 2015)
The world is still recovering from the most recent global recession associated with the 2008-09 financial crisis and the possibility of another downturn persists as the global economy struggles to regain lost ground. But, what is a global recession? What is a global recovery? What really happens during these episodes? As the debates about the recent global recession and the subsequent recovery have clearly shown, our understanding of these questions has been very limited. This book tracks the global business cycle through the destruction of a global recession to the renewal of recovery, drawing on four major episodes in the past half century. It defines key terms, documents the main features of a global recession and recovery, and describes the events that take place around these episodes. The book also puts the latest global recession and ongoing recovery in perspective. For more information, watch this YouTube trailer: https://www.youtube.com/watch?v=7PC1t_0RFog.